Student Worksheet Science Based On Process Image Of Light Concept For Learning In Junior High Schools - Muh. Zainuri; Sutarto Sutarto; Supeno Supeno; Indrawati Indrawati; Jekti Prihatin (Pancaran Pendidikan, 2017)
Student worksheet science based on process image is a printed material that presents a series of images of objects (objects, events, or phenomena), the images in the series between each other always appear to be relatively different in terms (state, position, shape, Combinations) which as a whole illustrate a coherent stage of events in a unified whole. A student worksheet is able to facilitate students in reviewing the material independently, so that materialised learning the science of student centred learning. The purpose of this study is to examine the use of student worksheet based on the image of light concept process for practical and effective junior high school student learning. This research design uses one group pretest-posttest design. The result of the research shows that learning activity is increasing up to reach 83,18%, and respondent gives a positive response with 'good' criterion. N-gain increased understanding of the concept of light by 0.628 on moderate criteria and supported with retention of 99.6%. The use of student worksheets based on the image of light concept process is practical and effective for improving students' understanding, as well as knowledge can be stored for longer in student memory.